Mapping and Assessment of Geological Lineaments with the Contribution of Earth Observation Data: A Case Study of the Zaer Granite Massif, Western Moroccan Meseta - Zoraa, Noura; Raji , Mohammed; El Hadi, Hassan; Maimouni, Soufiane; Si Mhamdi, Hicham; Reddad, Aicha; Zahour , Ghalem; Ait-Yazza, Achraf (Geomatics and Environmental Engineering, 2023)
The Zaer granitic massif is one of the most important Variscan granitoids in the Central Zone of the Western Moroccan Meseta. It is characterized by a deformation which is manifested by a network of fractures of different scales. Thanks to the technology currently available, many geological studies rely heavily on the mapping of geological lineaments, especially in structural geology. This has become more reliable with access to earth observation data using optical and radar sensors as well as the various remote sensing techniques. Therefore, the objective of this work is to determine the potential of Landsat 8, ASTER, Sentinel 2 and radar Sentinel 1 datasets using the automatic method to extract lineaments. Furthermore, this work focuses on quantitative lineament analysis to determine lineament trends and subsequently compare them with global and regional tectonic movement trends. The lineaments obtained through different satellite images were validated by including the shaded relief maps, the slope map, the correlation with the pre-existing faults in the geological maps as well as the field investigation. Comparison of these results indicates that Sentinel 1 imagery provides a better correlation between automated extraction lineaments and major fault zones. Thus, Sentinel 1 data is more effective in mapping geological lineaments. The final lineament map obtained from the VH and VV polarizations shows two major fault systems, mainly oriented NE-SW and NW-SE to NNW-SSE.